Combination therapy of atypical odontalgia with fluoxetine and clonazepam: Report of an effective prescription - Hamed Mortazavi; Maryam Baharvand; Amin Khodadoustan; Zahra Mansouri (Wolters Kluwer Medknow Publications, 2014)
Introduction: Atypical odontalgia (AO) is a subgroup of persistent idiopathic facial pain. We introduced a combination therapy of fluoxetine and clonazepam to treat AO. Case Report: A 30-year-old female with the chief complaint of severe pain (#8 based on Visual Analogue Scale( VAS)) in the site of extracted tooth #3 since 2 months ago was referred to the Department of Oral Medicine. The pain was of sharp quality continuing all day long and radiated to cervical muscles, forehead, and mandible of the ipsilateral side and contra lateral structures. The patient was treated with fluoxetine 20 mg/d and clonazepam 0.5 mg/d. The pain intensity was reported almost #0 when the patient was re evaluated 1 month after the first visit. An 8-month follow up revealed no sign of pain and discomfort on the affected site. Discussion: Combination therapy with clonazepam and fluoxetine has a positive effect in the treatment of AO.